Analisis Iklim Organisasi Terhadap Kepuasan Kerja Pada PT. Tiki Jalur Nugraha Ekakulir (JNE) Cabang Sukabumi - Silmia, Silmia; Samsudin, Acep; Sunarya, Erry (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
Employee job satisfaction at work will have a high sense of enthusiasm and work participation so that it will continue to improve their performance, so as to create work morale, dedication, love, and employee discipline to the company. One of the factors that influence job satisfaction is the work environment, a conducive and comfortable atmosphere in an organization such as the positive attitude of employees which is reflected in good relationships among colleagues will certainly help improve performance. The purpose of this study was to determine the effect of organizational climate on employee job satisfaction of PT. Tiki jalur Nugraha Ekakulir Branch Sukabumi and the object of research are employees of PT. Tiki Jalur Nugraha Ekakulir Branch Sukabumi. This research method uses quantitative methods using simple linear regression analysis. With 86 respondents as employees using the IBM SPSS Version 24 software. The results of the organizational climate T test showed that the tcount in this study was 8,186 with a significant value of 0,000, then a significant value of 0,000 <compared to 0.05, it can be concluded that the organizational climate variable positive effect on job satisfaction at PT. Tiki Jalur Nugraha Ekakulir Branch Sukabumi.